ANALYZING THE IMPACT OF SOCIAL MEDIA MARKETING CAMPAIGNS ON BRAND AWARENESS AND CUSTOMER ENGAGEMENT - G. Purushothaman, Dr. P. Manivannan (Chelonian Research Foundation, 2023)
The abstract of this study provides a concise overview of the research conducted on the impact of social media marketing campaigns on brand awareness and customer engagement. The study aimed to analyze various factors that influence the success of these campaigns, including frequency of posts, content type, platform selection, target audience segmentation, hashtag usage, and timing of posts. Through an extensive literature review and analysis of existing studies in this field, it was found that an effective social media marketing campaign can significantly enhance brand awareness and increase customer engagement. The frequency at which posts are made plays a crucial role in maintaining visibility and capturing audience attention. Moreover, the content type should be tailored to resonate with the target audience's interests and preferences. Platform selection is vital for reaching specific demographics effectively. By segmenting the target audience based on their characteristics or behaviors, marketers can personalize their messaging and connect with them more meaningfully. Utilizing relevant hashtags amplifies reach by tapping into trending conversations within online communities. Furthermore, timing plays a pivotal role in maximizing campaign effectiveness. Posting during peak activity periods when users are most active increases visibility and engagement potential. Keywords: Social media marketing campaigns, Brand awareness, customer engagement, Frequency of posts ,Content type, Platform selection, Target audience segmentation, Hash tag usage, Timing of posts